PENGARUH DISIPLIN KERJA, GAYA KEPEMIMPINAN, DAN KOMPENSASI TERHADAP KINERJA PADA KARYAWAN DI PT GRAHA SERVICE INDONESIA CABANG SURAKARTA DENGAN MOTIVASI SEBAGAI VARIABEL MODERATING - Sutarno, Novi Sri Rejeki Indra Putri, SL. Triyaningsih & (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2016)
The purpose of this research was: 1) to analyze the significance of the influence of the working discipline, leadership styles, motivation and compensation on performance on employees at PT Graha Service Indonesia (GSI) of Surakarta. 2) to analyze whether the motivation to moderate the influence of work discipline, leadership style and compensation on performance on employees at PT Graha Service Indonesia (GSI) of Surakarta. Research methods method using survey data, the type of data used was qualitative and quantitative data, the source data used the primary data and the data of skunder. Population and sample in this research is part of the employee's service in PT Graha Service Indonesia (GSI) of Surakarta. Methods of data collection were used: questionnaires, observation and documentation. Technique of data analysis used the test of validity, reliability test, test the assumptions of classical, linear regression analysis of multiple test, t test, F test and the determination of the coefficient of absolute difference. The research results obtained conclusions: there is a significant influence of the working discipline, leadership styles, motivation and compensation on performance of employees on the employees of PT Graha Service Indonesia (GSI) of Surakarta. Motivation does not moderate the influence of work discipline, leadership style and compensation on performance on employees at PT Graha Service Indonesia (GSI) of Surakarta.Keywords: labor discipline, leadership styles, motivation, compensation, performance